The Effect of a video-based resistance band training on the strength and range of motion of individuals with early stage-CTS - Caladiao, Claire Chelcee R. 1998-; Manlangit, Pastor Jr. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Clerical work is associated with long hours of sitting in an office chair in front of the computer. The highly sedentary nature of clerical work has long been proven to contribute to the development of different diseases such as Carpal Tunnel Syndrome (CTS). CTS is characterized by pain, itching numbness, and tingling in the palm of the hand, thumb, index, middle, and ring fingers. The condition is usually caused by increased pressure on the median nerve. Prolonged exposure of the workers to non-neutral positions of the wrist when using the keyboard and the mouse might reduce the space in the tunnel, which causes pressure, leading to CTS. Thus, the study aims to employ a workplace- and video-based resistance band training program to strengthen the handgrip and improve the range of motion of the clerical workers. 18 participants from different departments of UP were filtered from a pool of 54 workers with early stage-CTS through the two screening methods: the Boston Carpal Tunnel Scale Questionnaire, and provocative testing. The 18 participants were randomized into two groups: the experimental group (n = 10) and the control group (n = 8). The pre-and post-tests include a handgrip strength test using a handgrip dynamometer, and ROM testing of the different wrist movements using a goniometer. After the 5-week program, a significant increase was observed in the left-hand flexion and radial deviation of the experimental group, as well as their right-hand extension, ulnar deviation, and handgrip strength, while no significant increase was found in the control group. A significant difference was revealed in the left hand-flexion and radial deviation, and in the right-hand extension between the experimental and control group.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Carpal tunnel syndrome; Carpal tunnel syndrome -- Exercise therapy; Exercise bands (Exercise equipment).